2018
DOI: 10.1186/s12859-018-2332-x
|View full text |Cite
|
Sign up to set email alerts
|

Noise cancellation using total variation for copy number variation detection

Abstract: BackgroundDue to recent advances in sequencing technologies, sequence-based analysis has been widely applied to detecting copy number variations (CNVs). There are several techniques for identifying CNVs using next generation sequencing (NGS) data, however methods employing depth of coverage or read depth (RD) have recently become a main technique to identify CNVs. The main assumption of the RD-based CNV detection methods is that the readcount value at a specific genomic location is correlated with the copy num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…13 – 17 ). Copy number calling has been reported to be noisy for several data types 27 , 28 , and we observed that quantitative comparisons between CNA profiles are sensitive to: (1) the thresholds and baselines used to define gains and losses; (2) the dynamic range of copy number values from each platform; and (3) the differential impacts of normal cell contamination for different measurements. To control for such systematic biases, we assessed the similarity between two CNA profiles using the Pearson correlation of their log 2 [copy number ratio] values across the genome in 100-kilobase (kb) windows.…”
Section: Resultsmentioning
confidence: 96%
“…13 – 17 ). Copy number calling has been reported to be noisy for several data types 27 , 28 , and we observed that quantitative comparisons between CNA profiles are sensitive to: (1) the thresholds and baselines used to define gains and losses; (2) the dynamic range of copy number values from each platform; and (3) the differential impacts of normal cell contamination for different measurements. To control for such systematic biases, we assessed the similarity between two CNA profiles using the Pearson correlation of their log 2 [copy number ratio] values across the genome in 100-kilobase (kb) windows.…”
Section: Resultsmentioning
confidence: 96%
“…13 – 17). Copy number calling has been reported to be noisy for several data types 39,40 , and we observed that quantitative comparisons between CNA profiles are sensitive to: (1) the thresholds and baselines used to define gains and losses, (2) the dynamic range of copy number values from each platform, and (3) the differential impacts of normal cell contamination for different measurements. To control for such systematic biases, we assessed the similarity between two CNA profiles using the Pearson correlation of their log 2 (CN ratio) values across the genome in 100kb windows.…”
Section: Resultsmentioning
confidence: 96%
“…However, accurate CNV detection in targeted NGS data remains challenging. Bias and noise in NGS coverage data, derived from various sources during library preparation, capture, and sequencing, distort the association between copy numbers and read coverages [38,39]. Despite the excellent sensitivity and specificity of our CNV flagging algorithm, we pseudogene specific variants according to the reference sequence are also found in real gene, and vice versa [36].…”
Section: 4mentioning
confidence: 96%
“…Further optimization of NGS library preparation procedures, such as using normalized high-quality DNA for library preparation, may improve coverage uniformity and, therefore, CNV specificity. In addition, employing recently described denoising methods based on a signal processing technique may enhance the detection accuracy of our CNV algorithm [38]. Another factor that may confound accurate CNV analysis is a processed pseudogene if its existence is unknown.…”
Section: 4mentioning
confidence: 99%